PENGEMBANGAN TADRIBAT PEMBELAJARAN ISTIMA’ BUKU AL ‘ARABIYAH LIL HAYAH BERBASIS ONLINE - Abdullah Ubaid; Taaib Maghfur (UIN Maulana Malik Ibrahim Malang, 2021)
The development of online-based Arabic learning media is a requirement in this modern era to improve the quality of learning. The purpose of this research is (1) to produce an exercise of online-based listening learning in Al 'Arabiyah Lil Hayah Book. (2) Analyzing the feasibility of online listening learning exercises in the Al 'Arabiyah Lil Hayah Book.This study uses a research and development model according to Borg and Gall with 10 stages, namely: (1) research and information collecting, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision (6) main field testing, (7) operasional product revision, (8) operasional field testing, (9) final product revision, (10) dissemination and implementation.The output of this research and development is an exercise of online-based listening learning in Al 'Arabiyah Lil Hayah Book which can be accessed by users very easily via a computer or smartphone connected to an internet network without having to download certain applications, but simply typing the website address ppb.uin-malang.ac.id/alh in the user's device browser.Based on the results of the research that has been carried out by the researcher, it can be concluded that the exercise of online-based listening learning in Al 'Arabiyah Lil Hayah Book is feasible to use. This refers to the data obtained by researchers from the results of the questionnaire analysis by the Arabic learning media experts, namely Dr. Danial Hilmi, M.Pd. as well as respondents from PKPBA students in the preliminary field testing, main field testing and operasional field testing.